13C‐chloromethane incubations provide evidence for novel bacterial chloromethane degraders in a living tree fern. (27th June 2021) - Kröber, Eileen; Wende, Sonja; Kanukollu, Saranya; Buchen‐Tschiskale, Caroline; Besaury, Ludovic; Keppler, Frank; Vuilleumier, Stéphane; Kolb, Steffen; Bringel, Françoise
Summary: Chloromethane (CH3 Cl) is the most abundant halogenated volatile organic compound in the atmosphere and contributes to stratospheric ozone depletion. CH3 Cl has mainly natural sources such as emissions from vegetation. In particular, ferns have been recognized as strong emitters. Mitigation of CH3 Cl to the atmosphere by methylotrophic bacteria, a global sink for this compound, is likely underestimated and remains poorly characterized. We identified and characterized CH3 Cl‐degrading bacteria associated with intact and living tree fern plants of the species Cyathea australis by stable isotope probing (SIP) with 13 C‐labelled CH3 Cl combined with metagenomics. Metagenome‐assembled genomes (MAGs) related to Methylobacterium and Friedmanniella were identified as being involved in the degradation of CH3 Cl in the phyllosphere, i.e., the aerial parts of the tree fern, while a MAG related to Sorangium was linked to CH3 Cl degradation in the fern rhizosphere. The only known metabolic pathway for CH3 Cl degradation, via a methyltransferase system including the gene cmuA, was not detected in metagenomes or MAGs identified by SIP. Hence, a yet uncharacterized methylotrophic cmuA ‐independent pathway may drive CH3 Cl degradation in the investigated tree ferns.